USE OF ART PEDAGOGY IN THE PROCESS OF ADAPTATION OF IMMIGRANT STUDENT TO THE UNIVERSITY - Khilya, Anna; Kolosova, Olena; Blashkova, Olena; Hodlevska, Valentyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The document contains materials on working with first-year students, who have changed their place of residence in connection with the military action in their homeland. The focus of the paper is on the issue of adaptation of immigrant student to the conditions of the university.We carried out a psychological and pedagogical research using diagnostics of the socio-psychological adaptation of a group of immigrant students (self-acceptance, acceptance of others, emotional comfort, integrity, desire to dominate). We used: Test of Personal Adjustment (C. Rogers, R. Dymond), Eysenck Personality Inventory (H. Eysenck), UCLA Loneliness Scale (D. Russell), Taylor Manifest Anxiety Scale, TMAS (J. Taylor), method of «Three Trees» E. Klessmani to study the characteristics of inter-group and family relations.The article also analyzed and presented art pedagogy means to help this group of students to overcome difficulties in adapting to the new conditions of life. Namely: elements of a four-component author's program for working with personal orientations and values using the means of art pedagogy in the process of studying basic disciplines